Influence of Authentic Leadership on Innovation Performance: The Role of Knowledge Sharing and Organizational Commitment - Siagian, Melisa; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
In dynamic business environments, innovation is the key to organizational success. PT. Indokemika Group recognizes leadership's pivotal role in driving innovation. The study aims to assess Authentic Leadership's impact on Innovation Performance, with Explicit and Tacit Knowledge Sharing and Organizational Commitment as mediators. Analyzing data from 180 respondents, Structural Equation Model (SEM) and Sobel Test were utilized. Findings reveal that authentic leadership and tacit knowledge sharing significantly influence innovation performance through organizational commitment mediation. However, organizational commitment doesn't mediate the link between authentic leadership and explicit knowledge. Implications entail nurturing authentic leadership, promoting knowledge-sharing culture, and fostering robust organizational commitment.